Biofuel characteristics and combustion emissions of poultry litter and lignocellulosic biomass. Issue 3 (21st November 2020) - Ozdemir, Saim; Demir, Meryem Sekine
Abstract: Broiler chicken industry generate different kinds of organic wastes mainly poultry litters (PL), which presenting high energy potential, but significant incineration burdens due to the mineral compositions. In the present study, the combustion potential of PL and locally available biomass co‐combustion candidates were evaluated based on proximate, ultimate, ash constitute, and exhaust gas emission. High heating values measured for PL samples were in the range of 13.5–14.6 MJ/kg and low heating values were 12.9–13.6 MJ/kg, respectively. The ultimate analysis result of PL was as follows; C (46.5 ± 1.3%), O (44.8 ± 0.7%), H (3.6 ± 0.3%), N (3.9 ± 0.3%), and S (0.9 ± 0.1%). Ash deposit challenging minerals were abundant in PL, in contrasting to the lignocellulosic biomass; wood residue (WR), hazelnut shell (HS), corn stalk (CS), and giant reed (GR), which can serve mitigation potential. High nitrogen and sulfur concentrations in PL had significantly increased the NO x and SO2 emissions but confirming related standards. Despite the high exhaust gas and ash emissions, the energy recovery practices of PL co‐combustion with lignocellulosic biomas allow environmentally safe management option for PL.